Microimaging of transient guest profiles to monitor mass transfer in nanoporous materials - Kärger, Jörg; Binder, Tomas; Chmelik, Christian; Hibbe, Florian; Krautscheid, Harald; Krishna, Rajamani; Weitkamp, Jens (Nature materials, 2014)
Microimaging techniques, such as interference and infrared microscopy, can be used as a tool to directly monitor guest profiles within nanoporous materials. Observation of the variation in these profiles leads to unprecedented insight into transport phenomena, including intracrystalline diffusion and surface permeation. The intense interactions of guest molecules with the pore walls of nanoporous materials is the subject of continued fundamental research. Stimulated by their thermal energy, the guest molecules in these materials are subject to a continuous, irregular motion, referred to as diffusion. Diffusion, which is omnipresent in nature, influences the efficacy of nanoporous materials in reaction and separation processes. The recently introduced techniques of microimaging by interference and infrared microscopy provide us with a wealth of information on diffusion, hitherto inaccessible from commonly used techniques. Examples include the determination of surface barriers and the sticking coefficient's analogue, namely the probability that, on colliding with the particle surface, a molecule may continue its diffusion path into the interior. Microimaging is further seen to open new vistas in multicomponent guest diffusion (including the detection of a reversal in the preferred diffusion pathways), in guest-induced phase transitions in nanoporous materials and in matching the results of diffusion studies under equilibrium and non-equilibrium conditions.